Development of Pusat Tuisyen Pilihan Tepat Management System - Kwa, Yee Zhen; Mohd Safar, Noor Zuraidin (Applied Information Technology And Computer Science, 2022)
As a famous Tuition Centre, Pusat Tuisyen Pilihan Tepat had encountered two main problems, which are the inefficient manual management system and lack of platform for viewing the latest notice and information. Thus, this study is conducted with the objective to design, develop, and test an efficient web-based Tuition Centre Management System with the purpose of improving the management process of Pusat Tuisyen Pilihan Tepat. The Agile Model is used as the methodology to conduct the study and PHP Programming Language is used to develop the proposed system. The functional requirements, non-functional requirements, and UML diagrams of the proposed system will be identified. As a result, a web-based Tuition Centre management system named Pusat Tuisyen Pilihan Tepat Management System will be developed successfully so that the problems encountered can be resolved. With the developed proposed system, the management process of the Tuition Centre can be improved due to its efficiency.